The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1096/fj.09-137042
|View full text |Cite
|
Sign up to set email alerts
|

Protein interactions involving the γ2 large cytoplasmic loop of GABA A receptors modulate conductance

Abstract: Native GABA(A) channels display a single-channel conductance ranging between approximately 10 and 90 pS. Diazepam increases the conductance of some of these native channels but never those of recombinant receptors, unless they are coexpressed with GABARAP. This trafficking protein clusters recombinant receptors in the membrane, suggesting that high-conductance channels arise from receptors that are at locally high concentrations. The amphipathic (MA) helix that is present in the large cytoplasmic loop of every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…a-Helix Is Required for Intracellular GlyR Modulation (Tudan et al, 2002;Everitt et al, 2009;Guzman et al, 2009;San Martin et al, 2012;Zhang et al, 2014). For instance, several structural studies of protein-Gbg interaction, including complexes between Gbg and SIGK peptide (Davis et al, 2005;Lin and Smrcka, 2011), GRK2 (Tesmer et al, 2010;Thal et al, 2011) and phosducin (Loew et al, 1998;Gaudet et al, 1999), have reported participation of helical structures like those proposed in this study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…a-Helix Is Required for Intracellular GlyR Modulation (Tudan et al, 2002;Everitt et al, 2009;Guzman et al, 2009;San Martin et al, 2012;Zhang et al, 2014). For instance, several structural studies of protein-Gbg interaction, including complexes between Gbg and SIGK peptide (Davis et al, 2005;Lin and Smrcka, 2011), GRK2 (Tesmer et al, 2010;Thal et al, 2011) and phosducin (Loew et al, 1998;Gaudet et al, 1999), have reported participation of helical structures like those proposed in this study.…”
Section: Discussionsupporting
confidence: 67%
“…Also, a potential helical structure in the N-terminal LIL region was predicted in silico in pharmacologic studies of ethanol using small synthetic peptides derived from these regions (Guzman et al, 2009;San Martin et al, 2012). The presence of these helical structures is likely to serve for protein-protein interactions of the type previously proposed for other proteins Everitt et al, 2009;Chin et al, 2013;Shim et al, 2013;Alexander et al, 2014) and antagonized by small peptides having helical structures Representative glycine-evoked current traces (15 mM) in the absence and presence of 100 mM ethanol in a1-LIL-g2. (F) Effects of 100 mM ethanol on a1-GlyR and chimera a1-LIL-g2 in terms of percent of potentiation by 100 mM ethanol of 15 mM glycine-evoked currents.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the helical structure content was slightly lower than that previously reported for the intracellular loop domain of the α3 subunit suggesting a high conservation [163,167]. The helical structure described in the intracellular loop domain of α1 GlyRs may be required for protein/protein interactions as previously described for other protein complexes [186,187] or for peptides having the helical structure [168,169,187]. In this regard, numerous studies have reported the involvement of helical structures in the interaction sites such as complexes between Gβγ and peptides SlGK, GRK2 or phosducin [89,92,188].…”
Section: Mechanisms Of Ethanol Modulation On Glyrsmentioning
confidence: 72%
“…Patch electrodes contained (mM): 138 choline chloride, 0.3 KCl, 7 MgCl 2 , 10 TES (pH 7.3). Peptides were dissolved in DMSO (final concentration ≤ 0.01%), diluted to the required concentration with external solution and applied to the patch by exposing the pipette tip to flow tubes containing the test solutions (Everitt et al ., 2009). Currents were recorded with an Axopatch 200A or 200B current‐to‐voltage converter, filtered at 5–10 kHz and digitized at a frequency of 10–50 kHz using a Data Translation data acquisition card (DT3001‐PGL, Data Transition Inc, Marlboro, MA, USA) interfaced with an IBM compatible computer.…”
Section: Methodsmentioning
confidence: 99%